PERSEPSI MASYARAKAT BOGOR TERHADAP IKLAN YOUTUBE GRAB - Muslim Muslim (Media Bahasa, Sastra, dan Budaya Wahana, 2020)
AbstractThis study aims to analyze the perception of the Baranangsiang village community on Youtube Grab.  The study uses three variables which consist of two independent variables, community characteristics and Grab ads, and one dependent variable, perception of society is cognitive, affective and conative.This research was conducted in the Baranangsiang village with a population of about 22,825 people, conducted in October 2018 to May 2019. This study used a random sampling technique, the meaning of taking a random sample to the community of Baranangsiang village with a background of various kinds of education, occupation and age with a total of 100 respondents. Data analysis techniques used in this study are descriptive statistical analysis techniques and non-parametric statistical analysis. To measure the variables that have a nominal scale researchers use the Chi-square formula. So the researcher wants to see the perception of the Baranang-Siang village community on Grab ads on Youtube "there is a Grab in your city"The results obtained from this study are the Perception of the Baranangsiang Urban Village of Bogor on the Grab advertisement "There is a Grab in your city" can be said to be Positive with a high number of people strongly agreeing about the question of placing an advertisement at the beginning of a video on YouTube and the media that Grab uses to advertise .Keywords: Community, perception, Youtube and  Grab